Attenuated relationship between cardiac output and oxygen uptake during high-intensity exercise - Trinity, J. D.; Lee, J. F.; Pahnke, M. D.; Beck, K. C.; Coyle, E. F. (Acta Physiologica, 2012)
Recent findings have challenged the belief that the cardiac output (CO) and oxygen consumption (VO2) relationship is linear from rest to maximal exercise. The purpose of this study was to determine the CO and stroke volume (SV) response to a range of exercise intensities, 40-100% of VO2max, during cycling.